A surveillance study of antibiotic use in Pondicherry- 2012 - ., Revathysaravanan; Muthukumar, G.L. Arun (International Journal of Basic & Clinical Pharmacology, 2017)
Background: An alarming increase in antibiotic use and antimicrobial resistance especially in India is reported by WHO based on the reports from 5 pilot projects. As WHO and GARP India Working GroupState have stressed the importance ofrepeated co-ordinate surveillance to monitor, this study is undertaken in Pondicherry with the objectives of identifying Commonly used antibiotics, the most exposed age group in Pondicherry and the determining factors for inappropriate use of antibiotics among professionals and community. Methods: A surveillance study was done by using convenient sampling technique on 50 physicians and 100 people in community in the form of questionnaires after getting informed consent. The role of pharmacy was not includeddue to possible non reliability. The results are expressed by analyzing the data using descriptive statistics. Results: Experience and cost had been the main deciding factors for choosing the antibiotic for prescription. Third generation Cephalosporin was more prescribed and adults were exposed more to antibiotics with 81.56% and 75% from urban and rural respectively. Self medication was practiced by 14 out of 100 participants and more than 75% were not aware about proper use of antibiotics. Conclusions: No significant difference was observed in prescribing pattern among doctors of various qualifications from both urban and rural setup and lack of knowledge about proper use of antibiotics was seen in community. Hence it is essential to create awareness by means of public education programmes, media and CME targeting both rural and urban areas.